Geopolitical Security Concerns: A Catalyst for Russia’s Reengagement of Africa in Relations - Taiwo, Matthew Tope; Ademuyiwa, Akin (RIRAI Publisher, 2024)
Russia, also in the garb of the Union of Soviet Socialist Republics, had a record of a long-standing relations with Africa, the relationship that incidentally took a cold turn at the instance of the disintegration of the Soviet Union in the 1990s, as Russia prioritized stabilizing its domestic issues as the successor of the Soviet’s legacy. The emergence of the 21st century came with the post-Cold War security threat to Russian geopolitical space especially from its cold war rivals and hostile bordering states thus, prompting the conscientious efforts by Russia to review its foreign policy towards African alignment. The new Russia-Africa relations have generated a lot of interest by researchers, who have addressed the issue from a wide range of views, some of which included political, ideology, technical and economic. Cognizant of the geopolitical security concerns, which is observed as the primary basis for its new African relations, this research aims to examine Russian reengagement of Africa in relations adopting geostrategic theory. Data are gathered from secondary sources. The research is qualitative and framed within the scope of Russia-Africa security relations from 2014, following its annexation of Crimea, which marked a new phase of hostility between Russia and some North Atlantic Treaty Organisation allied countries. To achieve its strategic goal in Africa, Russia needs to pursue a comprehensive cooperation in other areas of direct investment that could offer African countries reciprocal paybacks that meet their national interests farther than concentrating on military aspect to achieving a personal goal.